Design and Implementation of a Real-Time Measurement Uncertainty Monitoring System for Orifice Gas Meters Using a Human–Machine Interface - Philip Christian Muli; Sagita Rohman; Nugroho Budi Widodo (Program Studi Teknik Elektronika Politeknik Negeri Malang, 2026)
Orifice Gas Meter (OGM) systems are widely used in the oil and gas industry for gas flow measurement. In Indonesia, OGM systems employed for custody transfer applications are designed and operated in accordance with American Gas Association Report No. 3 and the Decree of the Director General of Consumer Protection and Trade Compliance No. 17 of 2025. Accurate gas flow measurement using an OGM system requires numerous physical parameters, including differential pressure, static pressure, temperature, fluid density, pipe diameter, and other instrument characteristics. Consequently, OGM systems must comply with the maximum allowable measurement uncertainty requirement of 1.0% at 95% of confident level. The evaluation of measurement uncertainty is a complex task that must be performed periodically by OGM operators. This study aims to design and implement a real-time measurement uncertainty monitoring system based on a Human–Machine Interface (HMI). The proposed methodology includes HMI interface development, integration with a flow computer through the Modbus communication protocol, and validation through gas flow simulation. The results demonstrate that the developed HMI system is capable of displaying measurement uncertainty information in real time with a high level of agreement compared to the standard Microsoft Excel-based calculation tool developed by the Directorate of Metrology, Ministry of Trade. The proposed system can assist OGM operators throughout Indonesia in evaluating measurement performance and supporting more accurate operational decision-making.